Parasites and forage as determinants of body condition and population size in an imperiled ungulate - Benjamin J. Padilla; Oscar Alejandro Aleuy; Petter Jacobsen; Andy Dobson; Shelly Lachish; Susan Kutz; Mathieu Pruvot (Ecological Modelling, 2026)

Relationship between the siring capacity of beef bulls and their behaviour in multi-sire breeding groups measured by remote monitoring technologies - Vinicius A. Camargo; Edmond A. Pajor; Mathieu Pruvot; Sayeh Bayat; James C. Cross; Jennifer M. Pearson (Theriogenology, 2026)

Interaction risk between invasive wild pigs and livestock: Implications for potential infectious disease transmission in Alberta, Canada - Luis G. Salazar; Hannah McKenzie; Rob Deardon; Kim M. Pepin; Ryan Brook; Javier Bahamon; Cristina Neva; Mathieu Pruvot (Preventive Veterinary Medicine, 2026)

A new contactless method for local water content measurement applied for food product - Lison Pruvot; Theo Chavatte; Celia Sanz; Mathieu Delample; Mathilde Roze; Martine Crepin; Marie Marthe Groz; Alain Sommier (Innovative Food Science & Emerging Technologies, 2026)

Strengthening biodiversity conservation and One Health through ranger monitoring of wildlife health in protected areas - Diego Montecino‐Latorre; Sarah H. Olson; Emily Denstedt; Luis Guerra; Paulo Colchao‐Claux; Lucy Keatts; Aristide Andrianarimisa; Lovasoa Rabarisoa; Manfredo Martínez; Sophalrachana Kong; Devin Vorn; Zeveyda Jhancy Segura; et al. (Conservation Biology, 2026)
The lack of wildlife health (WH) surveillance systems leaves critical gaps in biodiversity conservation and One Health protection. Integrating rangers patrolling protected areas (PAs) into WH monitoring represents a cost‐effective and scalable opportunity to address these gaps at key human–wildlife interfaces and nature strongholds. For the past 2.5 years, organizations across 4 countries have collaborated to pilot this integration. The approach involved establishing a practical definition of health event for rangers patrolling PAs, developing a referential form tailored for rangers to document these events, training key country actors to identify and record health events on this form, merging this form with local forms used by rangers to record other events of interest observed during their patrols (e.g., illegal logging), and training rangers to identify and document health events with the modified local form. We examined 4 case studies involving dozens of PAs in different countries with different languages and local partners. The recording of health events was supported by the Spatial Monitoring And Reporting Tool, SMART, which provides the modified form for rangers on mobile devices and enabled standardized recording of events. Currently, over 200 rangers across more than 50 PAs have been trained, and more than 1000 health events have been recorded. This provides early evidence that rangers could enhance WH monitoring and strengthen biodiversity conservation, ultimately fostering One Health. This initiative lays important groundwork for overcoming key barriers (e.g., lack of personnel and funding) to establishing functional WH surveillance systems in PAs. Still, specific data infrastructure, human resources, and institutional support are needed. It will be important to evaluate the limitations of ranger‐collected data and align monitoring goals with the capabilities of rangers and data managers. Expansion to additional PAs is planned, alongside efforts to integrate ranger‐collected data into multisectoral One Health frameworks.

Wildlife health perceptions and monitoring practices in globally distributed protected areas - Diego Montecino‐Latorre; Mathieu Pruvot; Sarah H. Olson (Conservation Biology, 2025)
The status of health monitoring practices in protected areas (PAs) is largely unknown, but potential gaps could undermine biodiversity conservation at these key sites. There is also a lack of baseline information regarding local perceptions of wildlife, human, and livestock health relevance that could affect health monitoring implementation in PAs. To address these deficiencies, we conducted a web‐based survey of data managers from PAs worldwide. Specifically, we assessed perceptions regarding wildlife health and pathogen transmission between wildlife, humans, and livestock; the detection and documentation of unhealthy wildlife (injured, sick, and dead) and domestic animals in PAs; and health data management. Eighty‐six out of 128 responses were analyzed. Respondents considered WH relevant to the conservation goals of PAs (97%), and 98% of them confirmed that unhealthy wildlife are encountered. However, >50% and >20% of respondents claimed that injured or sick and dead animals were not recorded, respectively. When these animals were documented, the recording methods and information collected differed. Although respondents considered domestic animal presence common and a conservation concern, these animals or their health status may not be recorded (30% and 74%, respectively). Health data were often stored in a database, but paper forms and spreadsheets were also used. Responses suggested that valuable syndromic wildlife health surveillance data from PAs are not collected or are lost due to inadequate management and their value could be limited by a lack of standardized recording protocols.

Recycling lipases as a promising strategy in sponge cake development - Lison Pruvot; Aurélie Monié; Karine Clemens; Emile Perez; Sophie Franceschi; Stéphane Balayssac; Mathieu Delample (Food Research International, 2025)

WildHealthNet: Supporting the development of sustainable wildlife health surveillance networks in Southeast Asia - Mathieu Pruvot; Emily Denstedt; Alice Latinne; Alice Porco; Diego Montecino-Latorre; Kongsy Khammavong; Phonesavanh Milavong; Souchinda Phouangsouvanh; Manoly Sisavanh; Nguyen Thi Thanh Nga; Pham Thi Bich Ngoc; Vo Duy Thanh; et al. (Science of The Total Environment, 2023)

Extreme temperature event and mass mortality of insectivorous bats - Mathieu Pruvot; Julien Cappelle; Neil Furey; Vibol Hul; Huy Sreang Heng; Veasna Duong; Philippe Dussart; Paul Horwood (European Journal of Wildlife Research, 2019)

Can one detect atrial fibrillation using a wrist-type photoplethysmographic device? - Sibylle Fallet; Mathieu Lemay; Philippe Renevey; Célestin Leupi; Etienne Pruvot; Jean-Marc Vesin (Medical & Biological Engineering & Computing, 2019)